Using Print Media to Facilitate Luganda Language Teaching and Learning for Authentic Learning - Masembe, Edward; Athiemoolam, Logamurthie; Mdzanga, Nokhanyo (International Journal of Language and Literary Studies, 2024)
Luganda language teachers in Uganda have promoted the use of traditional language teaching strategies which are characterised by the CCR (copy, cram and reproduce) practice. Whereas language instruction has greatly shifted from traditional language teaching approaches to modern ones, this has not been the case with Luganda language teaching. Within the context of this background and with the aim of addressing this issue, we conducted a qualitative study, using a participatory action research approach to explore how Luganda teachers could use communicative strategies with the support of a variety of print media to facilitate Luganda teaching and learning for authentic learning. This paper presents an overview of how participants planned lessons using diverse print media to facilitate Luganda teaching and learning for authentic learning. Data was collected through participant observation and focus group discussions (reflective sessions). The findings emerging from this study indicated that the use of print media to facilitate Luganda language teaching led to enhanced learner participation and critical engagement.